Enhancing Students' Reading Literacy through the Implementation of Reading and Writing Across the Curriculum (RWAC) Using BukuAku - Amy Theresia Sipayung; Asep Herry Hernawan; Ahmad Fajar Fadlillah (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
This study evaluated the effectiveness of BukuAku, an interactive digital library application, in enhancing elementary school students’ reading literacy through the Reading and Writing Across the Curriculum (RWAC) approach. As digital learning tools become increasingly integral in early education, this study aimed to assess the impact of BukuAku on students’ reading comprehension using a quantitative research design. A quasi-experimental one-group pretest–posttest design was implemented involving 30 third-grade students over a four-month intervention period (January–April 2025). Two main instruments were employed in this study. The first instrument was the Lumina Testing Service (LTS), a Lexile-based quantitative reading assessment tool that is widely used internationally and supported by documented validity and reliability. The second was BukuAku, a digital library that provided leveled digital texts, audio narration, and quizzes to support the learning process. Reading proficiency was measured using the LTS before and after the intervention. Statistical analysis using a paired samples t-test revealed a significant increase in students’ Lexile scores, from a mean of 700.17 (SD = 26.375) in the pretest to 832.33 (SD = 39.277) in the posttest. These results demonstrate a substantial improvement in reading comprehension following the intervention. The findings support the efficacy of integrating digital literacy tools with cross-curricular reading and writing approaches to strengthen reading comprehension in early grades. This study contributes to the empirical literature on educational technology integration and highlights the value of structured, interactive literacy interventions. Future research is recommended to explore long-term impacts and broader implementation across diverse educational context.